Artificial Intelligence in Islamic Education: Opportunities and Challenges in the Digital Era - Pratama, Arizqi Ihsan; Muhammad, Muhd Rosydi (Madania: Jurnal Kajian Keislaman, 2025)
This article examines the application of artificial intelligence (AI) in Islamic education as a response to the challenges and opportunities presented by the digital era. Using a qualitative library research method, the study explores literature related to the integration of technology within Islamic educational systems. AI is considered capable of improving educational quality through personalized learning approaches, technology-based curriculum development, and enhanced administrative efficiency. In this context, AI can enrich the learning experience by supporting interactive, flexible, and student-centered education. However, the implementation of AI also faces various challenges, including infrastructure limitations, insufficient teacher training, and ethical issues such as the protection of students' personal data. The study finds that the integration of AI into Islamic education in Indonesia has already begun in several institutions, although its adoption remains uneven. Therefore, supportive policies, targeted training programs, and cross-sector collaboration among government bodies, educational institutions, and technology developers are essential. In conclusion, AI holds significant potential to improve the effectiveness of Islamic education, but its implementation must be approached with caution to ensure alignment with Islamic moral and ethical values. This article provides strategic recommendations to encourage the ethical, adaptive, and sustainable use of AI in the Islamic education ecosystem. Artikel ini mengkaji penerapan kecerdasan buatan (artificial intelligence/AI) dalam pendidikan Islam sebagai respons terhadap tantangan dan peluang di era digital. Penelitian ini menggunakan metode studi pustaka kualitatif dengan menelaah literatur yang membahas integrasi teknologi dalam sistem pendidikan Islam. AI dinilai mampu meningkatkan kualitas pembelajaran melalui pendekatan yang dipersonalisasi, pengembangan kurikulum berbasis teknologi, serta efisiensi dalam manajemen pendidikan. Dalam konteks ini, AI dapat memperkaya proses pembelajaran yang interaktif, fleksibel, dan sesuai dengan karakteristik peserta didik. Namun, implementasi AI juga menghadapi berbagai tantangan, seperti keterbatasan infrastruktur, minimnya pelatihan bagi pendidik, serta isu etika dan perlindungan data pribadi peserta didik. Studi ini menemukan bahwa integrasi AI dalam pendidikan Islam di Indonesia telah dimulai di sejumlah lembaga pendidikan, namun penerapannya masih belum merata. Oleh karena itu, dibutuhkan kebijakan yang mendukung, program pelatihan, serta kolaborasi lintas sektor antara pemerintah, institusi pendidikan, dan pengembang teknologi. Kesimpulannya, AI memiliki potensi besar dalam meningkatkan efektivitas pendidikan Islam, namun implementasinya harus dilakukan secara bijak agar tetap sejalan dengan nilai-nilai moral dan etika Islam. Artikel ini menawarkan rekomendasi strategis guna mendorong pemanfaatan AI secara etis, adaptif, dan berkelanjutan dalam ekosistem pendidikan Islam.